STRATEGI KEPALA SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN - Nurasiah Nurasiah (Jurnal Ilmiah Didaktika, 2012)
A strategy for a school headmaster is the most decisive factor in succeeding school’s quality improvement. This study aims at describing a main strategy planning, implementation, supervision and barriers in educational quality improvement. The study used a qualitative approach in descriptive methods. The data collection were used are observation, interview and documentation. The subjects of the study are the school committee, school head masters, teachers and Students. The result of the study shows that: 1) the main strategy planning in school quality improvement is by involving all school personnel, in which the head master of the school give an opportunity to the teachers to engage in quality planning, the head master of the school cooperate with the committee in formulating the school budget. 2) Head master strategy in improving the teaching quality is placing the teaching professionally, to learn an appropriate curriculum, to assist and to give suggestion to the teachers, as well as new student test implementation. 3) Strategy of the head master of the school in controlling school quality being conducted is using teaching supervision group controlling and individual techniques on quality improvement activities. 4) Some barriers on the implementation of the head master of the school quality are that the head master of the school could not spend the time and control all the school activities. The teachers are lack of ability to operate the advance school facility. The students’ evaluations which involved students’ parents who often do not welcome their sons’ shortcomings. This case is the difficulty of the teachers to evaluate.